2021
DOI: 10.1111/inr.12724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Polish nurses' working conditions and patient safety during the COVID‐19 pandemic

Abstract: Aim To study the relationship between Polish nurses' working conditions and their attitudes towards patient safety during the COVID‐19 pandemic. Background Facing the COVID‐19 pandemic, caused by the SARS‐CoV‐2 virus, healthcare worldwide has been reorganised. How these changes affected patient safety for hospitalised persons is not well understood. Introduction Difficult working conditions related to the outbreak of the COVID‐19 pandemic may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
1
22
0
2
Order By: Relevance
“…This could be rationalized by feeling more sense of commitment and responsibility toward the community during the critical situation of spreading COVID‐19 cases. In contrast, a recent study found that the COVID‐19 pandemic has negative consequences on job satisfaction, teamwork climate, and work conditions among Polish nurses (Malinowska‐Lipień et al., 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…This could be rationalized by feeling more sense of commitment and responsibility toward the community during the critical situation of spreading COVID‐19 cases. In contrast, a recent study found that the COVID‐19 pandemic has negative consequences on job satisfaction, teamwork climate, and work conditions among Polish nurses (Malinowska‐Lipień et al., 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…Failure to recognise the crucial role of organisational and relational work factors in the psycho-emotional state of HCWs may unfairly blame symptomatic individuals for not showing sufficient resilience. To avoid it, healthy work environments need to foster an improved patient safety culture and wider changes to implemented health policies [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the pandemic, the workload of nurses, the number of patients they care for, and their working hours have increased. For this reason, the working conditions of nurses became even more difficult than before the pandemic ( Maraqa et al, 2020 ; Tan et al, 2020 ; Fernández-Castillo et al, 2021 ; Malinowska‐Lipień et al, 2022 ; Riguzzi & Gashi, 2021 ; Tengilimoğlu et al, 2021 ). These challenges caused nurses to become overtired and burnt out, which increased employee tension, anxiety, stress disorders, and sleep problems during the COVID-19 pandemic ( Maraqa et al, 2020 ; Lipien et al, 2021; Lai et al, 2020 ; Zheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%